#### Answer

\[{y^,} = 98x - 84\]

#### Work Step by Step

\[\begin{gathered}
y = \,{\left( {7x - 6} \right)^2} \hfill \\
Write\,\,as\,\,a\,\,product \hfill \\
y = \,\left( {7x - 6} \right)\,\left( {7x - 6} \right) \hfill \\
Use\,\,the\,\,product\,\,rule\,\,to\,\,find\,\,{y^,} \hfill \\
{y^,} = \left( {7x - 6} \right){\left( {7x - 6} \right)^,} + \,\left( {7x - 6} \right){\left( {7x - 6} \right)^,} \hfill \\
{y^,} = 2\left( {7x - 6} \right){\left( {7x - 6} \right)^,} \hfill \\
Then \hfill \\
{y^,} = 2\left( {7x - 6} \right)\,\left( 7 \right) \hfill \\
Multiplying \hfill \\
{y^,} = 14\,\left( {7x - 6} \right) \hfill \\
{y^,} = 98x - 84 \hfill \\
\end{gathered} \]